Physiological and immunological responses of birds and mammals to forest degradation: A meta-analysis. (August 2018) - Messina, Simone; Edwards, David P.; Eens, Marcel; Costantini, David
Abstract: Dramatic changes in species composition have been found following selective logging and forest fragmentation. The different responses of bird species to these disturbances suggest that some species are more sensitive to environmental changes than others. Recent studies have suggested that the chances of species to adapt to new environments may be mediated by their stress physiology and immunity. We reviewed and performed a meta-analysis of studies that compared physiological and immunological endpoints of bird and mammal species between degraded (logged and fragmented) forests and undisturbed forests. We found that stress hormones and immunity markers show consistent changes in response to habitat degradation in birds and mammals. Higher physiological and immunological responses were found in those animals living in forests that were subjected to clear-cutting. Furthermore, we found that birds and species belonging to IUCN 'Threatened' categories exhibited significantly larger effect size estimates than mammals and 'Least Concern' species, respectively. Our meta-analysis revealed that changes in the production of stress hormones and in some immune traits are a significant consequence of forest disturbance. Physiology and immunity might be two important mediators of the adaptiveness of a given species to changing forests.